Local limit theorems taking into account large deviations in the case when Cramer’s condition does not hold - Nagaev, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. В. Нагаев. Локальные предельные теоремы с учетом больших уклонений, когда не выполнено условие Крамера A. Nagajevas. Lokalinės ribinės teoremos dideliems atsilenkimams, kai nepatenkinta Kramerio sąlyga